GREB1 is an estrogen receptor-regulated tumour promoter that is frequently expressed in ovarian cancer. Issue 44 (1st November 2018) - Hodgkinson, Kendra; Forrest, Laura; Vuong, Nhung; Garson, Kenneth; Djordjevic, Bojana; Vanderhyden, Barbara
Abstract Estrogenic hormone replacement therapy increases the risk of developing ovarian cancer, and estrogen promotes tumour initiation and growth in mouse models of this disease. GREB1 (Growth regulation by estrogen in breast cancer 1) is an ESR1 (estrogen receptor 1)-upregulated protein which may mediate estrogen action. GREB1 knockdown prevents hormone-driven proliferation of several breast and prostate cancer cell lines and prolongs survival of mice engrafted with ovarian cancer cells, but its mechanism of action remains unclear. In this study, we explored GREB1 function in ovarian cancer. GREB1 overexpression in ovarian cancer cell lines increased cell proliferation and migration and promoted a mesenchymal morphology associated with increasedCol1a2, which encodes a collagen I subunit. GREB1 knockdown inhibited proliferation and promoted an epithelial morphology associated with decreasedCol1a2 . In human tissues, GREB1 was expressed in all ESR1-expressing tissues throughout the normal female reproductive tract, in addition to several tissues that did not show ESR1 expression. In a TMA of ovarian cancer cases, GREB1 was expressed in 75–85% of serous, endometrioid, mucinous, and clear cell carcinomas. Serous, endometrioid, and mucinous ovarian cancers were almost always positive for either ESR1 or GREB1, suggesting a possible reliance on signalling through ESR1 and/or GREB1. Targeting GREB1 may inhibit tumour-promoting pathways both downstream and independent of ESR1 and is therefore a possible treatment strategy worthy of further investigation.